Antibacterial activity of bacteriocin produced from Lactobacillus and Lactococcus (Funded Work) - ARUNAVA DAS,; M. E. SINDUJA,; K. HARSHADHA,; J. BINDHU,; R. BALAKRISHNARAJA, (International Journal of Pharma and Bio Sciences, 2017)
Bacteriocins from bacteria inhibit the growth of similar or closely related bacterial strains. Present investigation was focused on to check the antibacterial activity of bacteriocin produced from Lactobacillus and Lactococcus bacteria against various pathogens of food spoilage and bovine mastitis. A total of 62 (15.93%) Lactobacillus and 22 (5.65%) Lactococcus isolates were tentatively identified from 389 commercial food products by using morphological, biochemical and molecular characterization. All the isolates were further confirmed has L. plantarum [22 (5.65%)] and L. acidophilus [18 (4.62%)] and Lactococcus lactis [22 (5.65%)] by polymerase chain reaction. In PCR, recA gene (318bp) and 16s-23s rRNA interspecific spacer regions (575bp) were amplified from the isolates of L. plantarum and L. acidophilus respectively, whereas, gadB (602bp) gene was amplified from Lactococcus lactis. The optimal conditions for the extraction and partial purification of bacteriocin were standardized by using ammonium sulphate precipitation and sephadex column chromatography respectively. Bactericidal activity of all bacteriocin producing Lactobacillus and Lactococcus isolates were tested against six major indicator bacteria of food spoilage and bovine mastitis like Listeria monocytogenes, Escherichia coli, Salmonella enterica Typhimurium, Staphylococcus aureus, Streptococcus agalactiae and Staphylococcus epidermis. The crude bacteriocin produced anaerobically by L. acidophilus isolates after 96hrs of incubation at 37°C showed higher antibacterial activity than L. plantarum and Lactococcus lactis. The purified bacteriocin showed significant<s>ly</s> increase in the zone of inhibition against Staphylococcus aureus and Streptococcus agalactiae than other bacteria. Present investigation suggested that the PCR is a simple, rapid and reliable method of diagnosis of Lactobacillus and Lactococcus bacteria up to species level. The purified bacteriocin produced from L. acidophilus was found to have inhibitory action against the Gram positive and Gram negative pathogens in foodborne and bovine mastitis .